Hubungan Media Sosial dan Game Online dengan Hasil Belajar Siswa - Ritonga, Lila Marito; Putra, Darma (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article analyzes the relationship between social media and online games and the Islamic religious education learning outcomes of students at the Private Junior High School of the Republic of Indonesia Teachers Association (PGRI) 4 in Jambi City. This article comes from quantitative research using hypothesis testing with the product moment correlation test. Data collection techniques for social media and online games are carried out by distributing questionnaires distributed directly by researchers and documentation. The population is all students of class VII and class VIII of the Private Junior High School of the Republic of Indonesia Teachers Association (PGRI) 4 Jambi City, totaling 66 students. Data analysis techniques include data tabulation, validity test, reliability test, normality test, and hypothesis test. The research results show that: (1) The first working hypothesis is accepted with a relationship strength of 25%. (2) The second working hypothesis is accepted with a relationship strength of 82%. (3) The third working hypothesis is accepted with a relationship strength of 82%. Artikel ini menganalisis bagaimana hubungan media sosial dan game online dengan hasil belajar pendidikan agama Islam siswa Sekolah Menengah pertama Swasta Persatuan Guru Republik Indonesia (PGRI) 4 di Kota Jambi. Artikel ini berasal dari penelitian kuantitatif dengan menggunakan uji hipotesis dengan uji korelasi product moment. Teknik pengumpulan data untuk media sosial dan game online dilakukan dengan penyebaran angket yang disebarkan langsung oleh peneliti dan dokumentasi. Populasinya adalah seluruh siswa kelas VII dan kelas VIII Sekolah Menengah pertama Swasta Persatuan Guru Republik Indonesia (PGRI) 4 Kota Jambi yang berjumlah 66 siswa. Teknik analisis data meliputi tabulasi data, uji validitas, uji realibilitas, uji normalitas, dan uji hipotesis. Hasil penelitian menunjukkan bahwa : (1) Hipotesis kerja pertama diterima dengan kekuatan hubungan 25%. (2) Hipotesis kerja kedua diterima dengan kekuatan hubungan 82%. (3) Hipotesis kerja ketiga diterima dengan kekuatan hubungan 82%.